m6A Regulatory Gene-Mediated Methylation Modification in Glioma Survival Prediction - Zhang, Guiyun; Zheng, Ping; Lv, Yisong; Shi, Zhonghua; Shi, Fei (Frontiers in Genetics, 2022)
The median survival of patients with gliomas is relatively short. To investigate the epigenetic mechanisms associated with poor survival, we analyzed publicly available datasets from patients with glioma. This analysis revealed 12 prognosis-related m6A regulatory genes that may be responsible for poor prognosis. These genes may be involved in genomic changes that are mostly enriched in oxidative phosphorylation, adipogenesis, hedgehog signaling, and Myc signaling. We reconstructed the risk model with univariate and multivariate Cox analyses and identified older age and m6A risk score as independent risk factors for predicting the prognosis of glioma patients and associated with immune infiltration in the glioma. In conclusion, m6A regulatory genes could serve as reliable biomarkers and potential targets for patient survival in gliomas.